Visual disability certification: A boon for the specially abled - Farooq, Shaheen; Kochar, Anju; Goyal, Rekha (International Journal Of Community Medicine And Public Health, 2021)
Background: Visual disability has deep emotional, social and economic impact. Rehabilitation of these individuals needs multidisciplinary approach to provide timely and complete support and improve the quality of life of the individual. Visual disability certification can be recognized as a mean by which social services of visually disabled can be coordinated. Objective was to analyze the demographics, causes and degree of visual disability and reasons of seeking disability certificate amongst visually disabled individuals attending ophthalmology OPD at a Tertiary Care Centre in India. Methods: A cross sectional study of patients seeking visual disability certificate was undertaken on 350 patients (567 eyes). Data were collected using pre set proforma. Cause of blindness was ascertained by complete ophthalmic examination and visually disability certificate was issued according to guidelines provided by Government of India. Results: Male female ratio was 1.9:1. Most of patients were from rural side, illiterate and unemployed. Most common age group was 16-30 years and financial and transport assistance was common reason for which certificate was sought. Corneal opacity was most common cause of blindness and visual impairment. Conclusions: Taking necessary preventive measures with the leading causes being identified can reduce the burden of visual impairment. On one hand increase in ophthalmic care and public education is needed to minimize the avoidable blindness rates ;on other hand strategies should be made to rehabilitate the individuals suffering from the unavoidable blindness. Benefits provided via visual disability certificate can play a pivotal role in rehabilitation of such patients.